2021
DOI: 10.1002/bin.1779
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of noncontingent reinforcement to treat mealtime problem behavior

Abstract: We evaluated the effects of noncontingent reinforcement (NCR) without escape extinction (EE) on problem behavior emitted by a young boy with autism spectrum disorder during meals. Results indicated that NCR (i.e., continuous access to a highly preferred activity) was effective in reducing problem behavior and moderately increasing food acceptance. Subsequently, we evaluated a total sessionbased thinning of the NCR schedule. Although problem behavior remained low during schedule thinning, differential reinforce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Results of these studies support the assumption that the inclusion of NCR provides beneficial effects for IMB and might sometimes reduce negative vocalizations. Berth et al also included an NCR‐alone condition, as did Luis et al (2021) and Silbaugh et al (2020). Previous research (e.g., Reed et al, 2004) has suggested NCR without escape extinction is insufficient to increase oral intake; however, two out of the three studies saw moderate effects on acceptance with NCR alone for some participants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results of these studies support the assumption that the inclusion of NCR provides beneficial effects for IMB and might sometimes reduce negative vocalizations. Berth et al also included an NCR‐alone condition, as did Luis et al (2021) and Silbaugh et al (2020). Previous research (e.g., Reed et al, 2004) has suggested NCR without escape extinction is insufficient to increase oral intake; however, two out of the three studies saw moderate effects on acceptance with NCR alone for some participants.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that NCR might occasionally increase acceptance, but the conditions under which this increase occurs are unknown. The participant in Luis et al (2021) consumed six foods but had a history of eating a more diverse diet. Berth et al (2019) reported that the participant who responded to NCR alone had inadequate oral intake, and she was in the 10th percentile for height and weight.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the terminal probe evaluation, therapists conducted schedule thinning and increased the S Δ period in a systematic stepwise fashion until reaching the respective terminal values listed above. The initial schedule-thinning steps implemented after the terminal probe evaluation were derived by identifying the latency of a participant to engage in problem behavior during the terminal probe evaluation and sub-Schedule thinning steps tracting 1 min (akin to approaches used in calculating reinforcer delivery schedules in noncontingent reinforcement; e.g.,Luis et al, 2021). Data were analyzed using proportions of baseline.…”
mentioning
confidence: 99%